Prawne aspekty gospodarowania nieruchomościami rolnymi w Polsce w latach 1918–2020 - Suchoń, Aneta (Komunizm: System - Ludzie - Dokumentacja, 2023)
The aim of the article was to evaluate the legal provisions on the management of agricultural real estate in terms of establishing and enlarging farms in the years 1918– 2020, as well as to indicate their impact on the agrarian structure in Poland. First, the rules for land real estate in the interwar period were presented, especially legal acts regulating the implementation of the land reform of 1920 and 1925. Then, the considerations focused on the land reform of 6 September 1944, including the transfer of land real estate by law to state, establishment of the State Land Fund and the way real estate was managed. Subsequently, the principles of managing agricultural land from the Agricultural Property Stock of the State Treasury and the restrictions in trade in private agricultural land under the Act on shaping the agricultural system were discussed. In summary the author stated, inter alia, that the shaping of the agrarian structure and the establishment and enlargement of agricultural farms in Poland were significantly influenced by land reform and the agricultural system, which changed in the 20th century. She also emphasized economic instruments since they largely contrib-uted to the improvement of the area structure of farms after Poland’s accession to the European Union (e.g. structural pensions, bonuses for young farmers, the possibility of using preferential loans for land and tax preferences in the agricultural tax related to the enlargement).